CONTRIBUTION OF SOCIAL CAPITAL, TRAINING, COMPETENCE, AND WORK EXPERIENCE TO EMPLOYEE PERFORMANCE (Study at Health Service Facility of RSUD Dr. Sayidiman Magetan) - Ardani, Risa; Suryantoro, Agustinus; Susilo, A. M. (Jurnal Aplikasi Manajemen, 2017)
This research aimed to find out the effect of social capital on the employee performance, to find out the effect of training on employee performance, to find out the effect of competence on employee performance, and to find out the effect of work experience on employee performance. This study was conducted in healthcare facilities of Regional General Hospital Dr. Sayidiman Magetan. The populations in this study were nurses at the Inpatient Dr Sayidiman Magetan Hospital totaling 519 people. The sampling technique employed in this research was proportionate stratified random sampling with the sample consisting of 115 employees, it's obtained from the sample size (n) = number of indicators (23) x 5. Techniques of collecting data used in this research were documentation, observation and questionnaire. Technique of analyzing data used was chi square analysis. The result of research showed that social capital affected significantly the employee performance. Training education affected significantly the employee performance. Competence affected significantly the employee performance in. Job experience affected significantly employee performance